src/HOL/Groebner_Basis.thy
author haftmann
Thu May 06 23:11:57 2010 +0200 (2010-05-06)
changeset 36720 41da7025e59c
parent 36716 b09f3ad3208f
child 36751 7f1da69cacb3
permissions -rw-r--r--
proper sublocales; no free-floating ML sections
wenzelm@23252
     1
(*  Title:      HOL/Groebner_Basis.thy
wenzelm@23252
     2
    Author:     Amine Chaieb, TU Muenchen
wenzelm@23252
     3
*)
wenzelm@23252
     4
wenzelm@23252
     5
header {* Semiring normalization and Groebner Bases *}
haftmann@28402
     6
wenzelm@23252
     7
theory Groebner_Basis
haftmann@36699
     8
imports Numeral_Simprocs Nat_Transfer
wenzelm@23252
     9
uses
haftmann@36699
    10
  "Tools/Groebner_Basis/normalizer.ML"
chaieb@23312
    11
  ("Tools/Groebner_Basis/groebner.ML")
wenzelm@23252
    12
begin
wenzelm@23252
    13
wenzelm@23252
    14
subsection {* Semiring normalization *}
wenzelm@23252
    15
haftmann@36700
    16
setup Normalizer.setup
wenzelm@23252
    17
haftmann@36712
    18
locale normalizing_semiring =
wenzelm@23252
    19
  fixes add mul pwr r0 r1
wenzelm@23252
    20
  assumes add_a:"(add x (add y z) = add (add x y) z)"
wenzelm@23252
    21
    and add_c: "add x y = add y x" and add_0:"add r0 x = x"
wenzelm@23252
    22
    and mul_a:"mul x (mul y z) = mul (mul x y) z" and mul_c:"mul x y = mul y x"
wenzelm@23252
    23
    and mul_1:"mul r1 x = x" and  mul_0:"mul r0 x = r0"
wenzelm@23252
    24
    and mul_d:"mul x (add y z) = add (mul x y) (mul x z)"
wenzelm@23252
    25
    and pwr_0:"pwr x 0 = r1" and pwr_Suc:"pwr x (Suc n) = mul x (pwr x n)"
wenzelm@23252
    26
begin
wenzelm@23252
    27
wenzelm@23252
    28
lemma mul_pwr:"mul (pwr x p) (pwr x q) = pwr x (p + q)"
wenzelm@23252
    29
proof (induct p)
wenzelm@23252
    30
  case 0
wenzelm@23252
    31
  then show ?case by (auto simp add: pwr_0 mul_1)
wenzelm@23252
    32
next
wenzelm@23252
    33
  case Suc
wenzelm@23252
    34
  from this [symmetric] show ?case
wenzelm@23252
    35
    by (auto simp add: pwr_Suc mul_1 mul_a)
wenzelm@23252
    36
qed
wenzelm@23252
    37
wenzelm@23252
    38
lemma pwr_mul: "pwr (mul x y) q = mul (pwr x q) (pwr y q)"
wenzelm@23252
    39
proof (induct q arbitrary: x y, auto simp add:pwr_0 pwr_Suc mul_1)
wenzelm@23252
    40
  fix q x y
wenzelm@23252
    41
  assume "\<And>x y. pwr (mul x y) q = mul (pwr x q) (pwr y q)"
wenzelm@23252
    42
  have "mul (mul x y) (mul (pwr x q) (pwr y q)) = mul x (mul y (mul (pwr x q) (pwr y q)))"
wenzelm@23252
    43
    by (simp add: mul_a)
wenzelm@23252
    44
  also have "\<dots> = (mul (mul y (mul (pwr y q) (pwr x q))) x)" by (simp add: mul_c)
wenzelm@23252
    45
  also have "\<dots> = (mul (mul y (pwr y q)) (mul (pwr x q) x))" by (simp add: mul_a)
wenzelm@23252
    46
  finally show "mul (mul x y) (mul (pwr x q) (pwr y q)) =
wenzelm@23252
    47
    mul (mul x (pwr x q)) (mul y (pwr y q))" by (simp add: mul_c)
wenzelm@23252
    48
qed
wenzelm@23252
    49
wenzelm@23252
    50
lemma pwr_pwr: "pwr (pwr x p) q = pwr x (p * q)"
wenzelm@23252
    51
proof (induct p arbitrary: q)
wenzelm@23252
    52
  case 0
wenzelm@23252
    53
  show ?case using pwr_Suc mul_1 pwr_0 by (induct q) auto
wenzelm@23252
    54
next
wenzelm@23252
    55
  case Suc
wenzelm@23252
    56
  thus ?case by (auto simp add: mul_pwr [symmetric] pwr_mul pwr_Suc)
wenzelm@23252
    57
qed
wenzelm@23252
    58
wenzelm@23252
    59
lemma semiring_ops:
wenzelm@23252
    60
  shows "TERM (add x y)" and "TERM (mul x y)" and "TERM (pwr x n)"
wenzelm@28856
    61
    and "TERM r0" and "TERM r1" .
wenzelm@23252
    62
wenzelm@23252
    63
lemma semiring_rules:
wenzelm@23252
    64
  "add (mul a m) (mul b m) = mul (add a b) m"
wenzelm@23252
    65
  "add (mul a m) m = mul (add a r1) m"
wenzelm@23252
    66
  "add m (mul a m) = mul (add a r1) m"
wenzelm@23252
    67
  "add m m = mul (add r1 r1) m"
wenzelm@23252
    68
  "add r0 a = a"
wenzelm@23252
    69
  "add a r0 = a"
wenzelm@23252
    70
  "mul a b = mul b a"
wenzelm@23252
    71
  "mul (add a b) c = add (mul a c) (mul b c)"
wenzelm@23252
    72
  "mul r0 a = r0"
wenzelm@23252
    73
  "mul a r0 = r0"
wenzelm@23252
    74
  "mul r1 a = a"
wenzelm@23252
    75
  "mul a r1 = a"
wenzelm@23252
    76
  "mul (mul lx ly) (mul rx ry) = mul (mul lx rx) (mul ly ry)"
wenzelm@23252
    77
  "mul (mul lx ly) (mul rx ry) = mul lx (mul ly (mul rx ry))"
wenzelm@23252
    78
  "mul (mul lx ly) (mul rx ry) = mul rx (mul (mul lx ly) ry)"
wenzelm@23252
    79
  "mul (mul lx ly) rx = mul (mul lx rx) ly"
wenzelm@23252
    80
  "mul (mul lx ly) rx = mul lx (mul ly rx)"
wenzelm@23252
    81
  "mul lx (mul rx ry) = mul (mul lx rx) ry"
wenzelm@23252
    82
  "mul lx (mul rx ry) = mul rx (mul lx ry)"
wenzelm@23252
    83
  "add (add a b) (add c d) = add (add a c) (add b d)"
wenzelm@23252
    84
  "add (add a b) c = add a (add b c)"
wenzelm@23252
    85
  "add a (add c d) = add c (add a d)"
wenzelm@23252
    86
  "add (add a b) c = add (add a c) b"
wenzelm@23252
    87
  "add a c = add c a"
wenzelm@23252
    88
  "add a (add c d) = add (add a c) d"
wenzelm@23252
    89
  "mul (pwr x p) (pwr x q) = pwr x (p + q)"
wenzelm@23252
    90
  "mul x (pwr x q) = pwr x (Suc q)"
wenzelm@23252
    91
  "mul (pwr x q) x = pwr x (Suc q)"
wenzelm@23252
    92
  "mul x x = pwr x 2"
wenzelm@23252
    93
  "pwr (mul x y) q = mul (pwr x q) (pwr y q)"
wenzelm@23252
    94
  "pwr (pwr x p) q = pwr x (p * q)"
wenzelm@23252
    95
  "pwr x 0 = r1"
wenzelm@23252
    96
  "pwr x 1 = x"
wenzelm@23252
    97
  "mul x (add y z) = add (mul x y) (mul x z)"
wenzelm@23252
    98
  "pwr x (Suc q) = mul x (pwr x q)"
wenzelm@23252
    99
  "pwr x (2*n) = mul (pwr x n) (pwr x n)"
wenzelm@23252
   100
  "pwr x (Suc (2*n)) = mul x (mul (pwr x n) (pwr x n))"
wenzelm@23252
   101
proof -
wenzelm@23252
   102
  show "add (mul a m) (mul b m) = mul (add a b) m" using mul_d mul_c by simp
wenzelm@23252
   103
next show"add (mul a m) m = mul (add a r1) m" using mul_d mul_c mul_1 by simp
wenzelm@23252
   104
next show "add m (mul a m) = mul (add a r1) m" using mul_c mul_d mul_1 add_c by simp
wenzelm@23252
   105
next show "add m m = mul (add r1 r1) m" using mul_c mul_d mul_1 by simp
wenzelm@23252
   106
next show "add r0 a = a" using add_0 by simp
wenzelm@23252
   107
next show "add a r0 = a" using add_0 add_c by simp
wenzelm@23252
   108
next show "mul a b = mul b a" using mul_c by simp
wenzelm@23252
   109
next show "mul (add a b) c = add (mul a c) (mul b c)" using mul_c mul_d by simp
wenzelm@23252
   110
next show "mul r0 a = r0" using mul_0 by simp
wenzelm@23252
   111
next show "mul a r0 = r0" using mul_0 mul_c by simp
wenzelm@23252
   112
next show "mul r1 a = a" using mul_1 by simp
wenzelm@23252
   113
next show "mul a r1 = a" using mul_1 mul_c by simp
wenzelm@23252
   114
next show "mul (mul lx ly) (mul rx ry) = mul (mul lx rx) (mul ly ry)"
wenzelm@23252
   115
    using mul_c mul_a by simp
wenzelm@23252
   116
next show "mul (mul lx ly) (mul rx ry) = mul lx (mul ly (mul rx ry))"
wenzelm@23252
   117
    using mul_a by simp
wenzelm@23252
   118
next
wenzelm@23252
   119
  have "mul (mul lx ly) (mul rx ry) = mul (mul rx ry) (mul lx ly)" by (rule mul_c)
wenzelm@23252
   120
  also have "\<dots> = mul rx (mul ry (mul lx ly))" using mul_a by simp
wenzelm@23252
   121
  finally
wenzelm@23252
   122
  show "mul (mul lx ly) (mul rx ry) = mul rx (mul (mul lx ly) ry)"
wenzelm@23252
   123
    using mul_c by simp
wenzelm@23252
   124
next show "mul (mul lx ly) rx = mul (mul lx rx) ly" using mul_c mul_a by simp
wenzelm@23252
   125
next
wenzelm@23252
   126
  show "mul (mul lx ly) rx = mul lx (mul ly rx)" by (simp add: mul_a)
wenzelm@23252
   127
next show "mul lx (mul rx ry) = mul (mul lx rx) ry" by (simp add: mul_a )
wenzelm@23252
   128
next show "mul lx (mul rx ry) = mul rx (mul lx ry)" by (simp add: mul_a,simp add: mul_c)
wenzelm@23252
   129
next show "add (add a b) (add c d) = add (add a c) (add b d)"
wenzelm@23252
   130
    using add_c add_a by simp
wenzelm@23252
   131
next show "add (add a b) c = add a (add b c)" using add_a by simp
wenzelm@23252
   132
next show "add a (add c d) = add c (add a d)"
wenzelm@23252
   133
    apply (simp add: add_a) by (simp only: add_c)
wenzelm@23252
   134
next show "add (add a b) c = add (add a c) b" using add_a add_c by simp
wenzelm@23252
   135
next show "add a c = add c a" by (rule add_c)
wenzelm@23252
   136
next show "add a (add c d) = add (add a c) d" using add_a by simp
wenzelm@23252
   137
next show "mul (pwr x p) (pwr x q) = pwr x (p + q)" by (rule mul_pwr)
wenzelm@23252
   138
next show "mul x (pwr x q) = pwr x (Suc q)" using pwr_Suc by simp
wenzelm@23252
   139
next show "mul (pwr x q) x = pwr x (Suc q)" using pwr_Suc mul_c by simp
huffman@35216
   140
next show "mul x x = pwr x 2" by (simp add: nat_number' pwr_Suc pwr_0 mul_1 mul_c)
wenzelm@23252
   141
next show "pwr (mul x y) q = mul (pwr x q) (pwr y q)" by (rule pwr_mul)
wenzelm@23252
   142
next show "pwr (pwr x p) q = pwr x (p * q)" by (rule pwr_pwr)
wenzelm@23252
   143
next show "pwr x 0 = r1" using pwr_0 .
huffman@35216
   144
next show "pwr x 1 = x" unfolding One_nat_def by (simp add: nat_number' pwr_Suc pwr_0 mul_1 mul_c)
wenzelm@23252
   145
next show "mul x (add y z) = add (mul x y) (mul x z)" using mul_d by simp
wenzelm@23252
   146
next show "pwr x (Suc q) = mul x (pwr x q)" using pwr_Suc by simp
huffman@35216
   147
next show "pwr x (2 * n) = mul (pwr x n) (pwr x n)" by (simp add: nat_number' mul_pwr)
wenzelm@23252
   148
next show "pwr x (Suc (2 * n)) = mul x (mul (pwr x n) (pwr x n))"
huffman@35216
   149
    by (simp add: nat_number' pwr_Suc mul_pwr)
wenzelm@23252
   150
qed
wenzelm@23252
   151
wenzelm@23252
   152
haftmann@36712
   153
lemmas normalizing_semiring_axioms' =
haftmann@36712
   154
  normalizing_semiring_axioms [normalizer
wenzelm@23252
   155
    semiring ops: semiring_ops
wenzelm@26314
   156
    semiring rules: semiring_rules]
wenzelm@23252
   157
wenzelm@23252
   158
end
wenzelm@23252
   159
haftmann@36712
   160
sublocale comm_semiring_1
haftmann@36712
   161
  < normalizing!: normalizing_semiring plus times power zero one
haftmann@36712
   162
proof
haftmann@36712
   163
qed (simp_all add: algebra_simps)
wenzelm@23252
   164
haftmann@36720
   165
declaration {* Normalizer.semiring_funs @{thm normalizing.normalizing_semiring_axioms'} *}
wenzelm@23573
   166
haftmann@36712
   167
locale normalizing_ring = normalizing_semiring +
wenzelm@23252
   168
  fixes sub :: "'a \<Rightarrow> 'a \<Rightarrow> 'a"
wenzelm@23252
   169
    and neg :: "'a \<Rightarrow> 'a"
wenzelm@23252
   170
  assumes neg_mul: "neg x = mul (neg r1) x"
wenzelm@23252
   171
    and sub_add: "sub x y = add x (neg y)"
wenzelm@23252
   172
begin
wenzelm@23252
   173
wenzelm@28856
   174
lemma ring_ops: shows "TERM (sub x y)" and "TERM (neg x)" .
wenzelm@23252
   175
wenzelm@23252
   176
lemmas ring_rules = neg_mul sub_add
wenzelm@23252
   177
haftmann@36712
   178
lemmas normalizing_ring_axioms' =
haftmann@36712
   179
  normalizing_ring_axioms [normalizer
wenzelm@26314
   180
    semiring ops: semiring_ops
wenzelm@26314
   181
    semiring rules: semiring_rules
wenzelm@26314
   182
    ring ops: ring_ops
wenzelm@26314
   183
    ring rules: ring_rules]
wenzelm@23252
   184
wenzelm@23252
   185
end
wenzelm@23252
   186
haftmann@36720
   187
sublocale comm_ring_1
haftmann@36720
   188
  < normalizing!: normalizing_ring plus times power zero one minus uminus
haftmann@36720
   189
proof
haftmann@36720
   190
qed (simp_all add: diff_minus)
wenzelm@23252
   191
haftmann@36720
   192
declaration {* Normalizer.semiring_funs @{thm normalizing.normalizing_ring_axioms'} *}
wenzelm@23252
   193
haftmann@36712
   194
locale normalizing_field = normalizing_ring +
chaieb@23327
   195
  fixes divide :: "'a \<Rightarrow> 'a \<Rightarrow> 'a"
chaieb@23327
   196
    and inverse:: "'a \<Rightarrow> 'a"
chaieb@30866
   197
  assumes divide_inverse: "divide x y = mul x (inverse y)"
chaieb@30866
   198
     and inverse_divide: "inverse x = divide r1 x"
chaieb@23327
   199
begin
chaieb@23327
   200
chaieb@30866
   201
lemma field_ops: shows "TERM (divide x y)" and "TERM (inverse x)" .
chaieb@30866
   202
chaieb@30866
   203
lemmas field_rules = divide_inverse inverse_divide
chaieb@30866
   204
haftmann@36712
   205
lemmas normalizing_field_axioms' =
haftmann@36712
   206
  normalizing_field_axioms [normalizer
wenzelm@26314
   207
    semiring ops: semiring_ops
wenzelm@26314
   208
    semiring rules: semiring_rules
wenzelm@26314
   209
    ring ops: ring_ops
chaieb@30866
   210
    ring rules: ring_rules
chaieb@30866
   211
    field ops: field_ops
chaieb@30866
   212
    field rules: field_rules]
chaieb@23327
   213
chaieb@23327
   214
end
chaieb@23327
   215
haftmann@36712
   216
locale normalizing_semiring_cancel = normalizing_semiring +
wenzelm@23252
   217
  assumes add_cancel: "add (x::'a) y = add x z \<longleftrightarrow> y = z"
wenzelm@23252
   218
  and add_mul_solve: "add (mul w y) (mul x z) =
wenzelm@23252
   219
    add (mul w z) (mul x y) \<longleftrightarrow> w = x \<or> y = z"
wenzelm@23252
   220
begin
wenzelm@23252
   221
wenzelm@23252
   222
lemma noteq_reduce: "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
wenzelm@23252
   223
proof-
wenzelm@23252
   224
  have "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> \<not> (a = b \<or> c = d)" by simp
wenzelm@23252
   225
  also have "\<dots> \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
wenzelm@23252
   226
    using add_mul_solve by blast
wenzelm@23252
   227
  finally show "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
wenzelm@23252
   228
    by simp
wenzelm@23252
   229
qed
wenzelm@23252
   230
wenzelm@23252
   231
lemma add_scale_eq_noteq: "\<lbrakk>r \<noteq> r0 ; (a = b) \<and> ~(c = d)\<rbrakk>
wenzelm@23252
   232
  \<Longrightarrow> add a (mul r c) \<noteq> add b (mul r d)"
wenzelm@23252
   233
proof(clarify)
wenzelm@23252
   234
  assume nz: "r\<noteq> r0" and cnd: "c\<noteq>d"
wenzelm@23252
   235
    and eq: "add b (mul r c) = add b (mul r d)"
wenzelm@23252
   236
  hence "mul r c = mul r d" using cnd add_cancel by simp
wenzelm@23252
   237
  hence "add (mul r0 d) (mul r c) = add (mul r0 c) (mul r d)"
wenzelm@23252
   238
    using mul_0 add_cancel by simp
wenzelm@23252
   239
  thus "False" using add_mul_solve nz cnd by simp
wenzelm@23252
   240
qed
wenzelm@23252
   241
chaieb@25250
   242
lemma add_r0_iff: " x = add x a \<longleftrightarrow> a = r0"
chaieb@25250
   243
proof-
chaieb@25250
   244
  have "a = r0 \<longleftrightarrow> add x a = add x r0" by (simp add: add_cancel)
chaieb@25250
   245
  thus "x = add x a \<longleftrightarrow> a = r0" by (auto simp add: add_c add_0)
chaieb@25250
   246
qed
chaieb@25250
   247
haftmann@36712
   248
declare normalizing_semiring_axioms' [normalizer del]
wenzelm@23252
   249
haftmann@36712
   250
lemmas normalizing_semiring_cancel_axioms' =
haftmann@36712
   251
  normalizing_semiring_cancel_axioms [normalizer
haftmann@36712
   252
    semiring ops: semiring_ops
haftmann@36712
   253
    semiring rules: semiring_rules
haftmann@36712
   254
    idom rules: noteq_reduce add_scale_eq_noteq]
wenzelm@23252
   255
wenzelm@23252
   256
end
wenzelm@23252
   257
haftmann@36712
   258
locale normalizing_ring_cancel = normalizing_semiring_cancel + normalizing_ring + 
chaieb@25250
   259
  assumes subr0_iff: "sub x y = r0 \<longleftrightarrow> x = y"
wenzelm@23252
   260
begin
wenzelm@23252
   261
haftmann@36712
   262
declare normalizing_ring_axioms' [normalizer del]
wenzelm@23252
   263
haftmann@36712
   264
lemmas normalizing_ring_cancel_axioms' = normalizing_ring_cancel_axioms [normalizer
wenzelm@23252
   265
  semiring ops: semiring_ops
wenzelm@23252
   266
  semiring rules: semiring_rules
wenzelm@23252
   267
  ring ops: ring_ops
wenzelm@23252
   268
  ring rules: ring_rules
chaieb@25250
   269
  idom rules: noteq_reduce add_scale_eq_noteq
wenzelm@26314
   270
  ideal rules: subr0_iff add_r0_iff]
wenzelm@23252
   271
wenzelm@23252
   272
end
wenzelm@23252
   273
haftmann@36720
   274
sublocale idom
haftmann@36720
   275
  < normalizing!: normalizing_ring_cancel plus times power zero one minus uminus
haftmann@36720
   276
proof
haftmann@36720
   277
  fix w x y z
haftmann@36720
   278
  show "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z"
haftmann@36720
   279
  proof
haftmann@36720
   280
    assume "w * y + x * z = w * z + x * y"
haftmann@36720
   281
    then have "w * y + x * z - w * z - x * y = 0" by (simp add: algebra_simps)
haftmann@36720
   282
    then have "w * (y - z) - x * (y - z) = 0" by (simp add: algebra_simps)
haftmann@36720
   283
    then have "(y - z) * (w - x) = 0" by (simp add: algebra_simps)
haftmann@36720
   284
    then have "y - z = 0 \<or> w - x = 0" by (rule divisors_zero)
haftmann@36720
   285
    then show "w = x \<or> y = z" by auto
haftmann@36720
   286
  qed (auto simp add: add_ac)
haftmann@36720
   287
qed (simp_all add: algebra_simps)
wenzelm@23252
   288
haftmann@36720
   289
declaration {* Normalizer.semiring_funs @{thm normalizing.normalizing_ring_cancel_axioms'} *}
wenzelm@23252
   290
haftmann@36712
   291
interpretation normalizing_nat!: normalizing_semiring_cancel
ballarin@29223
   292
  "op +" "op *" "op ^" "0::nat" "1"
huffman@35216
   293
proof (unfold_locales, simp add: algebra_simps)
wenzelm@23252
   294
  fix w x y z ::"nat"
wenzelm@23252
   295
  { assume p: "w * y + x * z = w * z + x * y" and ynz: "y \<noteq> z"
wenzelm@23252
   296
    hence "y < z \<or> y > z" by arith
wenzelm@23252
   297
    moreover {
wenzelm@23252
   298
      assume lt:"y <z" hence "\<exists>k. z = y + k \<and> k > 0" by (rule_tac x="z - y" in exI, auto)
wenzelm@23252
   299
      then obtain k where kp: "k>0" and yz:"z = y + k" by blast
nipkow@29667
   300
      from p have "(w * y + x *y) + x*k = (w * y + x*y) + w*k" by (simp add: yz algebra_simps)
wenzelm@23252
   301
      hence "x*k = w*k" by simp
huffman@35216
   302
      hence "w = x" using kp by simp }
wenzelm@23252
   303
    moreover {
wenzelm@23252
   304
      assume lt: "y >z" hence "\<exists>k. y = z + k \<and> k>0" by (rule_tac x="y - z" in exI, auto)
wenzelm@23252
   305
      then obtain k where kp: "k>0" and yz:"y = z + k" by blast
nipkow@29667
   306
      from p have "(w * z + x *z) + w*k = (w * z + x*z) + x*k" by (simp add: yz algebra_simps)
wenzelm@23252
   307
      hence "w*k = x*k" by simp
huffman@35216
   308
      hence "w = x" using kp by simp }
wenzelm@23252
   309
    ultimately have "w=x" by blast }
wenzelm@23252
   310
  thus "(w * y + x * z = w * z + x * y) = (w = x \<or> y = z)" by auto
wenzelm@23252
   311
qed
wenzelm@23252
   312
haftmann@36720
   313
declaration {* Normalizer.semiring_funs @{thm normalizing_nat.normalizing_semiring_cancel_axioms'} *}
wenzelm@23252
   314
haftmann@36712
   315
locale normalizing_field_cancel = normalizing_ring_cancel + normalizing_field
chaieb@23327
   316
begin
chaieb@23327
   317
haftmann@36712
   318
declare normalizing_field_axioms' [normalizer del]
chaieb@23327
   319
haftmann@36712
   320
lemmas normalizing_field_cancel_axioms' = normalizing_field_cancel_axioms [normalizer
chaieb@23327
   321
  semiring ops: semiring_ops
chaieb@23327
   322
  semiring rules: semiring_rules
chaieb@23327
   323
  ring ops: ring_ops
chaieb@23327
   324
  ring rules: ring_rules
chaieb@30866
   325
  field ops: field_ops
chaieb@30866
   326
  field rules: field_rules
chaieb@25250
   327
  idom rules: noteq_reduce add_scale_eq_noteq
wenzelm@26314
   328
  ideal rules: subr0_iff add_r0_iff]
wenzelm@26314
   329
chaieb@23327
   330
end
chaieb@23327
   331
haftmann@36720
   332
sublocale field 
haftmann@36720
   333
  < normalizing!: normalizing_field_cancel plus times power zero one minus uminus divide inverse
haftmann@36720
   334
proof
haftmann@36720
   335
qed (simp_all add: divide_inverse)
haftmann@28402
   336
haftmann@36720
   337
declaration {* Normalizer.field_funs @{thm normalizing.normalizing_field_cancel_axioms'} *}
haftmann@36712
   338
 
haftmann@36712
   339
haftmann@36712
   340
subsection {* Groebner Bases *}
haftmann@36712
   341
haftmann@36712
   342
lemmas bool_simps = simp_thms(1-34)
haftmann@36712
   343
haftmann@36712
   344
lemma dnf:
haftmann@36712
   345
    "(P & (Q | R)) = ((P&Q) | (P&R))" "((Q | R) & P) = ((Q&P) | (R&P))"
haftmann@36712
   346
    "(P \<and> Q) = (Q \<and> P)" "(P \<or> Q) = (Q \<or> P)"
haftmann@36712
   347
  by blast+
haftmann@36712
   348
haftmann@36712
   349
lemmas weak_dnf_simps = dnf bool_simps
haftmann@36712
   350
haftmann@36712
   351
lemma nnf_simps:
haftmann@36712
   352
    "(\<not>(P \<and> Q)) = (\<not>P \<or> \<not>Q)" "(\<not>(P \<or> Q)) = (\<not>P \<and> \<not>Q)" "(P \<longrightarrow> Q) = (\<not>P \<or> Q)"
haftmann@36712
   353
    "(P = Q) = ((P \<and> Q) \<or> (\<not>P \<and> \<not> Q))" "(\<not> \<not>(P)) = P"
haftmann@36712
   354
  by blast+
haftmann@36712
   355
haftmann@36712
   356
lemma PFalse:
haftmann@36712
   357
    "P \<equiv> False \<Longrightarrow> \<not> P"
haftmann@36712
   358
    "\<not> P \<Longrightarrow> (P \<equiv> False)"
haftmann@36712
   359
  by auto
haftmann@36712
   360
haftmann@36712
   361
ML {*
haftmann@36712
   362
structure Algebra_Simplification = Named_Thms(
haftmann@36712
   363
  val name = "algebra"
haftmann@36712
   364
  val description = "pre-simplification rules for algebraic methods"
haftmann@36712
   365
)
haftmann@28402
   366
*}
haftmann@28402
   367
haftmann@36712
   368
setup Algebra_Simplification.setup
haftmann@36712
   369
haftmann@36712
   370
declare dvd_def[algebra]
haftmann@36712
   371
declare dvd_eq_mod_eq_0[symmetric, algebra]
haftmann@36712
   372
declare mod_div_trivial[algebra]
haftmann@36712
   373
declare mod_mod_trivial[algebra]
haftmann@36712
   374
declare conjunct1[OF DIVISION_BY_ZERO, algebra]
haftmann@36712
   375
declare conjunct2[OF DIVISION_BY_ZERO, algebra]
haftmann@36712
   376
declare zmod_zdiv_equality[symmetric,algebra]
haftmann@36712
   377
declare zdiv_zmod_equality[symmetric, algebra]
haftmann@36712
   378
declare zdiv_zminus_zminus[algebra]
haftmann@36712
   379
declare zmod_zminus_zminus[algebra]
haftmann@36712
   380
declare zdiv_zminus2[algebra]
haftmann@36712
   381
declare zmod_zminus2[algebra]
haftmann@36712
   382
declare zdiv_zero[algebra]
haftmann@36712
   383
declare zmod_zero[algebra]
haftmann@36712
   384
declare mod_by_1[algebra]
haftmann@36712
   385
declare div_by_1[algebra]
haftmann@36712
   386
declare zmod_minus1_right[algebra]
haftmann@36712
   387
declare zdiv_minus1_right[algebra]
haftmann@36712
   388
declare mod_div_trivial[algebra]
haftmann@36712
   389
declare mod_mod_trivial[algebra]
haftmann@36712
   390
declare mod_mult_self2_is_0[algebra]
haftmann@36712
   391
declare mod_mult_self1_is_0[algebra]
haftmann@36712
   392
declare zmod_eq_0_iff[algebra]
haftmann@36712
   393
declare dvd_0_left_iff[algebra]
haftmann@36712
   394
declare zdvd1_eq[algebra]
haftmann@36712
   395
declare zmod_eq_dvd_iff[algebra]
haftmann@36712
   396
declare nat_mod_eq_iff[algebra]
haftmann@36712
   397
haftmann@36712
   398
use "Tools/Groebner_Basis/groebner.ML"
haftmann@36712
   399
haftmann@36720
   400
method_setup algebra = Groebner.algebra_method
haftmann@36720
   401
  "solve polynomial equations over (semi)rings and ideal membership problems using Groebner bases"
haftmann@28402
   402
haftmann@28402
   403
end